Ion plasma deposition and optical properties of SiC films - Semenov, A.V.; Lopin, A.V.; Puzikov, V.M.; Muto, Sh. (Functional Materials, 2005)
SiC films have been obtained by direct deposition from a C and Si ions flow at energy values in the 30 to 1.500 eV range. The films deposited at the substrate temperature 600 С were chemically and structurally disordered. The deposition energy increase resulted in a reduced optical slot of the film and increased Urbach parameter. The dependence is non-monotonous in the energy range 30-250 eV. The maximum value of the film optical gap (2.2 eV) is close to the band gap for cubic SiC (2.4 eV). The non-monotonic dependence of the film optical properties and structure parameters on the ion deposition energy in the 30-250 eV range can be connected with difference in behavior of C and Si sublattices in SiC under low-energy ion bombardment. Методом прямого осаждения из потока ионов C и Si с энергиями в диапазоне 30-1500 эВ получены пленки SiC. Осажденные при температуре подложек 600 С пленки являлись структурно и химически разупорядоченными. Повышение энергии осаждения приводило к уменьшению оптической щели пленок и увеличению параметра Урбаха. В диапазоне энергий 30-250 эВ эта зависимость является немонотонной. Максимальное значение оптической щели пленок (2.2 эВ) близко к величине запрещенной зоны кубического карбида кремния (2.4 эВ). Немонотонная зависимость оптических свойств и структурного состояния пленок от энергии осаждения ионов в диапазоне 30-250 эВ моГут быть связаны с различным поведением углеродной и кремниевой подрешеток карбида кремния в условиях низкоэнергетичной ионной бомбардировки.